Einfluss des Maulwurfs (Talpa europaea) auf die Wirksamkeit von Migrationsbarrieren zur Abwehr von Wühlmausschäden im Ökologischen Landbau - Walther, B.; Malevez, J.; Pelz, H.-J. (2007)
Water voles (Arvicola terrestris) and common voles (Microtus arvalis) cause substantial damage in organic fruit growing by gnawing at bark and roots of trees. To prevent the immigration of voles into orchards a mechanical drift fence was developed and successfully tested in 2002 and 2003. The effectiveness of the drift fence, consisting of wire mesh reaching 30 cm above the soil surface and up to 30 cm into the ground, was impaired by moles (Talpa europaea) undermining the fence. Voles used these tunnels to immigrate into the protected plots. In a new study supported by “Bundesprogramm Ökologischer Landbau” and carried out between 2004 and 2006, factors contributing to undermining of drift fences by moles were determined. The results of practical field experiments at three experimental sites in heavy soils indicate that drift fences at 50 cm depth may interrupt the immigration of voles and moles completely. However, as observed at a fourth study site, moles can impair the effectiveness of drift fences in lighter soils, especially in mighty loess soils and in fields with existing widestretched tunnel systems. Further trials should focus on the subterranean digging behaviour of moles and voles to adjust the underground construction of drift fences. At the current stage of development drift fences are not a stand alone method and should be combined with traditional control methods like trapping to achieve highly effective and time saving protection of organic orchards over long periods.